واقع الإنفاق الجاري في الوحدات الإدارية الحكومية في سوريا وترشيده " دراسة تحليلية " - الرضا, عقبة; الأمين, ماهر; ياســين, أيــام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نتيجة لتحول الاهتمام الأساسي للموازنة العامة للدولة عبر مراحل تطورها وانتقالها من مرحلة الموازنة التقليدية إلى موازنة البرامج والأداء ثم إلى موازنة التخطيط والبرمجة كان لابد من ضرورة الإصلاح المحاسبي الحكومي في النظام المحاسبي السوري أمام متطلبات التوسع الكبير في الإنفاق العام, وكان لابدّ من تزايد الاهتمام بترشيد الإنفاق الجاري في الوحدات الإدارية الحكومية كونها في الغالب هيئات خدمية تعتمد على النفقات الجارية في ظلّ نظامٍ محاسبي مقتصرٍ على الرقابة المالية والقانونية بغضّ النظر عن مدى تحقيق الكفاءة والفعالية مما يفسح المجال للإسراف وتبديد الموارد الحكومية, لذلك تناولت الباحثة واقع الإنفاق الجاري الحكومي بغرض تحديد مواطن الضعف في النظام المحاسبي الحكومي بهدف ترشيد الإنفاق وتوجيهه للتطوير والتنمية. إن الهدف من هذه الدراسة إلقاء الضوء على الدراسات والأنظمة المتطورة في المحاسبة الحكومية ومن ثم استعراض النظام المحاسبي الحكومي في سوريا بشكل تحليلي في ضوء المحدّدات الأساسية لمصداقية البيانات والعمليات المالية المتمثلة بالقانون المالي الأساسي الصادر بالمرسوم التشريعي /92/ لعام 1967 والأنظمة المالية النافذة, وتحليل واقع الموازنة السورية والإنفاق الجاري من الناحيتين التقديرية والتنفيذية مقارنة بالمؤشرات الاقتصادية, وقد تم دعم وتأكيد النتائج النظرية لهذه الدراسة بالدراسة العملية عن طريق طرح أسئلة على عينة من محاسبي الإدارات باعتبارهم الجهة الرقابية على تنفيذ و ضبط الإنفاق العام. As a result of the shift of basic emphasis of the government general budget through its stages of development and transformation from the traditional budget phase to a programmes and performance phase, then to planning and programming budget, the Syrian government's accountancy system needs correction. This is all the more so, because of the requirements of great expansion in government spending. It is also necessary to pay more attention to rationalization of government current expenditure in the administrative units as they are mostly service organizations that depend on current expenditure within an accountancy system, which is confined to financial and legal monitoring regardless of efficiency and effectiveness. Such a situation leads to overspending and waste of government resources. This study deals with the status of government current expenditure in order to rationalize expenditure and direct it towards development. The study seeks to cast light on studies and advanced systems of government accountancy in order to be able to analyze the Syrian government's accountancy system based on determiners of authenticity of financial records and data represented by basic the Financial Act issued in the legislative decree /92/ in 1967, together with the financial regulations already in force. The paper also reviews the status of the Syrian budget and current expenditure, both in approximate and real terms, relative to economic indicators. A lot of interviews with government accountants and questionnaires were done in support of the results of this study.